2009
DOI: 10.1021/bc900240z
|View full text |Cite
|
Sign up to set email alerts
|

Direct One-Step18F-Labeling of Peptides via Nucleophilic Aromatic Substitution

Abstract: Methods for the radiolabeling molecules of interest with [18F]-fluoride need to be rapid, convenient, and efficient. Numerous [18F]-labeled prosthetic groups, e.g., N-succinimidyl 4 [18F]-fluorobenzoate ([18F]-SFB), 4-azidophenacyl-[18F]-fluoride ([18F]-APF), and 1-(3-(2-[18F]fluoropyridin-3-yloxy)propyl)pyrrole-2,5-dione ([18F]-FpyMe), for conjugating to biomolecules have been developed. As the synthesis of these prosthetic groups usually requires multistep procedures, there is still a need for direct methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 29 publications
0
56
0
2
Order By: Relevance
“…Schirrmacher et al reported the direct radiolabeling of an organosilicon-modified peptide in an isotope exchange reaction (32). Several 1-step approaches for the facile 18 F labeling of peptides have been developed in our laboratories (19,31,33). In the present study, 18 F labeling of BAY 86-4367 was achieved in a single step via aromatic nucleophilic substitution.…”
Section: In Vivo Characterizationmentioning
confidence: 80%
See 4 more Smart Citations
“…Schirrmacher et al reported the direct radiolabeling of an organosilicon-modified peptide in an isotope exchange reaction (32). Several 1-step approaches for the facile 18 F labeling of peptides have been developed in our laboratories (19,31,33). In the present study, 18 F labeling of BAY 86-4367 was achieved in a single step via aromatic nucleophilic substitution.…”
Section: In Vivo Characterizationmentioning
confidence: 80%
“…The binding affinities of the nonradioactive 19 The inhibitor used for displacement was either nonradioactive 19 F-bombesin (1b) or neuromedin B (Sigma). The test compounds were dissolved in DMSO to produce 1 mM stock solutions and further diluted in incubation buffer to 2 pM-1,000 nM.…”
Section: In Vitro Characterizationmentioning
confidence: 99%
See 3 more Smart Citations